2008
DOI: 10.1186/1471-2180-8-156
|View full text |Cite
|
Sign up to set email alerts
|

Development of a real-time multiplex PCR assay for the detection of multiple Salmonella serotypes in chicken samples

Abstract: Background: A real-time multiplex PCR assay was developed for the detection of multiple Salmonella serotypes in chicken samples. Poultry-associated serotypes detected in the assay include Enteritidis, Gallinarum, Typhimurium, Kentucky and Dublin. The traditional cultural method according to EN ISO 6579:2002 for the detection of Salmonella in food was performed in parallel. The real-time PCR based method comprised a pre-enrichment step in Buffered Peptone Water (BPW) overnight, followed by a shortened selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
61
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(71 citation statements)
references
References 37 publications
6
61
0
4
Order By: Relevance
“…However Salmonella Typhimurium, Infantis, Kottbus, Kentuky, Minnesota were detected as higher prevalence by (Voss Rech et al, 2015Muammer et al, 2016and Abde-Rahim, 2016 respectively. It has been reported that invA gene is present only in Salmonella species and therefore is used as a golden marker in genetic diagnosis of Salmonella species as previously described (O'Regan et al, 2008). In our study the invA gene was detected with 100% in all examined Salmonella serovars, high prevalence rates of invA virulence gene in Salmonella serovars has also been reported by other workers (Karmi, 2013 andChaudhary et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
“…However Salmonella Typhimurium, Infantis, Kottbus, Kentuky, Minnesota were detected as higher prevalence by (Voss Rech et al, 2015Muammer et al, 2016and Abde-Rahim, 2016 respectively. It has been reported that invA gene is present only in Salmonella species and therefore is used as a golden marker in genetic diagnosis of Salmonella species as previously described (O'Regan et al, 2008). In our study the invA gene was detected with 100% in all examined Salmonella serovars, high prevalence rates of invA virulence gene in Salmonella serovars has also been reported by other workers (Karmi, 2013 andChaudhary et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
“…Table 2 shows the distribution of isolates and potential risk factors for the presence of Salmonella in chicken meat marketed at Ibague, Tolima. dISCuSSIon Salmonella spp., was isolated from 17.41% of chicken samples (47/270) marketed in Ibague, Tolima, and a number of serotypes were identified and confirmed by amplification of a fragment of the invA gene using PCR (Galan, Curtiss, 1991;Li et al, 2012;O'Regan et al, 2008;Shanmugasamy et al, 2011), a rapid and powerful technique used for Salmonella identification (Cardona-castro et al, 2007;Ibrahim et al, 2014;Molina et al, 2010;Tafida et al, 2013). Thus, this data is a representative estimation of the occurrence of Salmonella in a region with traditional poultry industry and it may indicate poor hygienic and disinfection practices, which have been associated with cross-contamination and recontamination of poultry carcasses (Carrasco et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The supernatant was discarded, and the cell pellets were suspended in 1 ml phosphate buffered saline (PBS), centrifuged at 15,330 × g for 5 min. The supernatant was again discarded, and the pellets were suspended in 50 μl sterile distilled water for DNA extraction (O'Regan et al 2008). The suspension was heated at 99 ºC for 10 min (Shanmugasamy et al, 2011), and then pelleted by centrifugation at 2,656 × g for 5 min.…”
Section: Dna Extractionmentioning
confidence: 99%